FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETERSEDIAAN LAYANAN TELEMEDICINE DI RUMAH SAKIT - Mira Eka Puspita; Dewi Laelatul Badriah; Mamlukah; Esty Febriani (Journal of Midwifery and Health Administration Research, 2023)
Background: Telemedicine usage data ranging from international data to the provincial level has increased but in contrast to the data in Kuningan Regency, hospitals that have used telemedicine services are 83% and those who have never used telemedicine services are 17%. Method: Type of Research using Mix Method with Sequential Explanatory design. The variables studied consist of facilities and infrastructure, costs, information technology and human resources. With a population of twelve hospitals, samples were obtained by means of Cluster Sampling, which is as many as four hospitals in Kuningan Regency. The instrument in this study quantitatively uses questionnaires with data analysis techniques is Spearman Rank and qualitative research instruments using interview guidelines, observation and documentation with analysis using triangulation of sources from several informants, namely main informants, key informants, supporting informants. Results: The results of Quantitative Research obtained facilities and infrastructure with a significant value of p = 0.029, Costs and Human Resources with a significant value of p = 0.030 and Information Technology with a significant value of p = 0.044 and for qualitative results of facilities and infrastructure there is already teleconsultation. Costs have not been sufficient for telemedicine facilities and infrastructure. Information technology requires development and human resources only need instructions from the leadership. Conclusion: Facilities and infrastructure, costs, information technology and human resources are significantly related to the availability of telemedicine services at Kuningan Regency Hospitals 2022.